(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study mainly aimed at clarifying the relationship between the mental image with its dimensions (the cognitive dimension, the emotional dimension, the behavioral dimension, and the social dimension), one of the dimensions of the golden marketing square, and the marketing performance of public commercial banks in the Syrian coast. The study followed the analytical descriptive approach, and a set of methods including reliance on secondary and primary data through a questionnaire designed and distributed to (127) respondents, (120) of which were retrieved, and (113) questionnaires were valid for analysis, and the research community consisted of a cadre Workers in commercial bank branches on the Syrian coast (branch manager, heads of departments, heads of divisions, and employees), then the SPSS program was relied upon as a tool for analyzing the available data. The study concluded that there is a significant relationship between the mental image with its dimensions (the cognitive dimension, the moral dimension, the behavioral dimension, the social dimension), one of the dimensions of the golden marketing square, and the marketing performance of public commercial banks in the coast, and the acceptance of regression equations for the three dimensions (the cognitive dimension in building the mental image and the dimension The emotional dimension in building the mental image and the behavioral dimension in building the mental image)..